Bias and Accuracy of Management Earnings Forecasts: An Evaluation of the Impact of Auditing* - MCCONOMY, BRUCE J. (Contemporary Accounting Research, 1998)
Abstract This paper assesses how the bias and accuracy of managers' earnings forecasts in prospectuses were affected by a 1989 regulation that required the forecasts to be audited by public accountants. Theory suggests that auditors' association with the forecasts would reduce positive (optimistic) bias, by reducing moral hazard. Regulators expected that the audit requirement would also improve the accuracy of the forecasts. Both predictions were tested using management earnings forecasts disclosed in prospectuses of Canadian initial public offerings. The results show that audited forecasts contained significantly less positive bias than reviewed forecasts, but there was only a marginally significant improvement in accuracy.